1994
DOI: 10.1128/jb.176.1.70-76.1994
|View full text |Cite
|
Sign up to set email alerts
|

Multicomplex cellulase-xylanase system of Clostridium papyrosolvens C7

Abstract: The cellulase system of Clostridium papyrosolvens C7 was fractionated by means of ion-exchange chromatography into at least seven high-molecular-weight multiprotein complexes, each with different enzymatic and structural properties. The molecular weights of the complexes, as determined by gel filtration chromatography, ranged from 500,000 to 660,000, and the isoelectric points ranged from 4.40 to 4.85. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis of the complexes showed that each complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 30 publications
4
47
1
Order By: Relevance
“…These complexes were co-eluted from a gel-filtration column in a high-molecular-mass fraction (>400 kDa), 'cellulosomal population', and separated by subjecting the high-molecular-mass fraction to anion-exchange chromatography. The elution profiles (subpopulations) obtained from anion-exchange chromatography showed that the cellulosome population was heterogeneous, in agreement with previous studies (Murashima et al, 2002a;Pohlschroder et al, 1994).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These complexes were co-eluted from a gel-filtration column in a high-molecular-mass fraction (>400 kDa), 'cellulosomal population', and separated by subjecting the high-molecular-mass fraction to anion-exchange chromatography. The elution profiles (subpopulations) obtained from anion-exchange chromatography showed that the cellulosome population was heterogeneous, in agreement with previous studies (Murashima et al, 2002a;Pohlschroder et al, 1994).…”
Section: Discussionsupporting
confidence: 78%
“…Recent transcriptional and proteomic studies show that different carbon sources in the C. cellulovorans culture medium have a significant effect on cellulosomal enzymic composition and activity (Han et al, 2003a(Han et al, , b, 2004b. Previously, Pohlschroder et al (1994Pohlschroder et al ( , 1995 found that the extracellular cellulase system of Clostridium papyrosolvens consisted of at least seven distinct high-molecular-mass protein complexes (500-660 kDa). All the complexes had endoglucanase-active protein subunits, but only two had xylanase-active subunits.…”
Section: Introductionmentioning
confidence: 99%
“…In C. papyrosolvens, a mesophilic anaerobe, the cellulase system (53) can be fractionated by ion-exchange chromatography into seven high-molecular-weight multiprotein complexes, with the molecular weights ranging from 500,000 to 600,000. Each complex has a different ultrastructure (269) and a unique profile of enzymatic activities (270). The common protein appearing in each fraction is a glycoprotein (M r ϭ 125,000) that lacks any enzymatic activity.…”
Section: Cellulosome Structurementioning
confidence: 99%
“…All seven multiprotein complexes have endoglucanase-active protein subunits, but only two of the complexes have xylanase-active subunits (16). Three of the multiprotein complexes hydrolyze crystalline cellulose (i.e., have Avicelase activity) (16).…”
mentioning
confidence: 99%
“…The extracellular cellulase-xylanase system of Clostridium papyrosolvens C7 comprises at least seven distinct high-molecular-weight multiprotein complexes (M r , 500,000 to 660,000), each with different polypeptide compositions and enzymatic properties (16). All seven multiprotein complexes have endoglucanase-active protein subunits, but only two of the complexes have xylanase-active subunits (16).…”
mentioning
confidence: 99%